The MAT-sf: Identifying Risk for Major Mobility Disability. (13th February 2015) - Rejeski, W. Jack; Rushing, Julia; Guralnik, Jack M.; Ip, Edward H.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary M.; Fielding, Roger A.; Newman, Anne B.; Tudor-Locke, Catrine; Gill, Thomas M.; et al.
Abstract : Background: The assessment of mobility is essential to both aging research and clinical geriatric practice. A newly developed self-report measure of mobility, the mobility assessment tool-short form (MAT-sf), uses video animations as an innovative method to improve measurement accuracy/precision. The primary aim of the current study was to evaluate whether MAT-sf scores can be used to identify risk for major mobility disability (MMD). Methods: This article is based on data collected from the Lifestyle Interventions and Independence for Elders study and involved 1, 574 older adults between the ages of 70–89. The MAT-sf was administered at baseline; MMD, operationalized as failure to complete the 400-m walk ≤ 15 minutes, was evaluated at 6-month intervals across a period of 42 months. The outcome of interest was the first occurrence of MMD or incident MMD. Results: After controlling for age, sex, clinic site, and treatment arm, baseline MAT-sf scores were found to be effective in identifying risk for MMD ( p < .0001). Partitioning the MAT-sf into four groups revealed that persons with scores <40, 40–49, 50–59, and 60+ had failure rates across 42 months of follow-up of 66%, 52%, 35%, and 22%, respectively. Conclusions: The MAT-sf is a quick and efficient way of identifying older adults at risk for MMD. It could be used to clinically identify older adults that are in need of intervention for MMD and provides a simple means for monitoring the status of patients' mobility, an important dimension of functional health.